Addressing the expected survival benefit for clinical trial design in metastatic castration-resistant prostate cancer: Sensitivity analysis of randomized trials. (February 2016) - Massari, Francesco; Modena, Alessandra; Ciccarese, Chiara; Pilotto, Sara; Maines, Francesca; Bracarda, Sergio; Sperduti, Isabella; Giannarelli, Diana; Carlini, Paolo; Santini, Daniele; Tortora, Giampaolo; Porta, Camillo; et al.
Highlights: All randomized clinical trials in with patients with metastatic castration-resistant prostate cancer received systemic therapy were considered. We used a meta-analytical approach to evaluate if the comparison of the trials' results may drive to biased survival estimations. Sensitivity analyses according to: 1) Therapeutic Strategy 2) Control arm and 3) Docetaxel timing were performed. The data reported suggest a differential benefit in overall survival according to the three factors analyzed. Abstract: We performed a sensitivity analysis, cumulating all randomized clinical trials (RCTs) in which patients with metastatic castration-resistant prostate cancer (mCRPC) received systemic therapy, to evaluate if the comparison of RCTs may drive to biased survival estimations. An overall survival (OS) significant difference according to therapeutic strategy was more likely be determined in RCTs evaluating hormonal drugs versus those studies testing immunotherapy, chemotherapy or other strategies. With regard to control arm, an OS significant effect was found for placebo-controlled trials versus studies comparing experimental treatment with active therapies. Finally, regarding to docetaxel (DOC) timing, the OS benefit was more likely to be proved in Post-DOC setting in comparison with DOC and Pre-DOC. These data suggest that clinical trial design should take into account new benchmarks such as the type of treatment strategy, the choice of the comparator and the phase of the disease in relation to the administration of standard chemotherapy.